ANALISIS USAHATANI JAMUR TIRAM PUTIH (Pleurotus ostreatus) DI KOTA PEKANBARU - Ermi Tety; Rachmawaty Sri Cintami; Yusmini ' (PEKBIS, 2017)
The purpose of this research is to analyze profit, break event point and efficiency ofoyster mushroom farming at Pekanbaru City. Population of this research are 10 (ten)oyster farmer. This research used survey method, to analyze the profit, break eventpoint and efficiency of oyster mushroom farmer used production cost formula,equipment depreciation formulafarm receipts formula and farming profits formula.Farming group determination of the amount of cultivated baglog, that are first groupis 1.000-2000 baglog, second group is >2.000-3.000 baglog, and the third Group is≥4.000-5.000 baglog. The result of this research showed average of farming incomefor one planting period, for first scale group is Rp.9.593.614,67 with BEP 318,20 Kg,for second group is Rp.17.384.527,78 with BEP 422,53 kg, and for third group areRp.29.125.910,00 with BEP 510,01 kg. Farming efficiency result for first group are1,93 it means output Rp.1,00 get profit Rp.0,93 and worthy to be developed, forsecond group are 2,21 it means output Rp.1,00 get profit Rp.1,21, and for third groupare 2,50 it means output Rp.1,00 get profit Rp.1,50 and this oyster mushroombusiness worthy to be continued.